2022
DOI: 10.1039/d2nr02361j
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional aliphatic fluorophores discovered as the luminescence origin in citric acid–urea carbon dots

Abstract: Carbon dots (CDs) are emerging as the material of choice in a range of applications due to their excellent photoluminescence properties, ease of preparation from inexpensive precursors, and low toxicity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…85 Then, Rogach's group proved that citrazinic acid is the main fluorophore responsible for the blue fluorescence of CDs prepared from CA and urea (recent reports also indicate the presence of oligomeric ureas, 5-oxopyrrolidine-3-carboxylic acid and other blue PL emitting species in these materials). [86][87][88][89] After careful evaluation of the optical properties of CDs obtained at different reaction times, it was concluded that at the initial stages of CD synthesis molecular fluorophores dominate their absorption and fluorescence characteristics, while for CDs prepared at longer reaction times more and more pronounced contribution of carbonized species becomes apparent (Fig. 2).…”
Section: Cbmfs In Blue-emitting Cdsmentioning
confidence: 99%
“…85 Then, Rogach's group proved that citrazinic acid is the main fluorophore responsible for the blue fluorescence of CDs prepared from CA and urea (recent reports also indicate the presence of oligomeric ureas, 5-oxopyrrolidine-3-carboxylic acid and other blue PL emitting species in these materials). [86][87][88][89] After careful evaluation of the optical properties of CDs obtained at different reaction times, it was concluded that at the initial stages of CD synthesis molecular fluorophores dominate their absorption and fluorescence characteristics, while for CDs prepared at longer reaction times more and more pronounced contribution of carbonized species becomes apparent (Fig. 2).…”
Section: Cbmfs In Blue-emitting Cdsmentioning
confidence: 99%
“…On the other hand, these aggregates could correspond to the CA-CDs themselves, as pointed out in several studies; thus, dialysis would not be the best option for their purification. , Beside dialysis, chromatography techniques provide a useful approach for understanding the composition of the raw CDs. Silica column chromatography, C18 reverse phase chromatography, , gel permeation chromatography, , size-exclusion chromatography, and ion exchange chromatography were exploited for the purification and/or characterization of the fluorophores for various CA-CD systems. Naturally, the efficiency of each of these methods strictly depends on the size and/or chemical nature of the individual components.…”
Section: General Aspects Of Ca-cdsmentioning
confidence: 99%
“…A systematic investigation of the effect of nine polar solvents on the CA/U-CD absorption, emission, and lifetimes was performed by Anjali Devi et al The complex trends in the CA/U-CD optical features were explained with the self-assembly of the fluorophores into different coexisting structures, i.e., H-aggregates, J-aggregates, and combinations of the two, whose presence was also supported by TEM characterization. , Moreover, in the work of Bhuyan et al, it is shown how the reversible formation of aggregates from water to acetone goes in parallel with the blue emission suppression in favor of the green emission enhancement, reflecting the fluorescence resonance energy transfer (FRET)-mediated energy migration from the blue fluorophores to the green fluorophores inside the aggregate . Finally, Yao et al performed the microwave-assisted irradiation of citric acid and urea, achieving isolation by means of reversed phase C18 column chromatography of the fluorophore 5-oxopyrrolidine-3-carboxylic acid (OPCA) . Intriguingly, this molecule is based on a nonconjugated amide ring and it belongs to a class of emissive compounds recently named nontraditional intrinsic luminophors (NTILs), i.e., organic structures that display photoluminescence in the absence of aromatic groups or metal centers.…”
Section: Ca-cd Classesmentioning
confidence: 99%
See 2 more Smart Citations